Domestic Millenial Tourist Attitude Toward Selection Four-star Rating Hotel in West Sumatera - Haris Ramadhan; Luthfi Marsa Salsabil; Jennyfer Jennyfer; Feri Ferdian (Home Journal., 2023)
This study aims to analyze the domestic millenial tourist attitude toward selection four star rating hotel in West Sumatera. This study uses a quantitative methodology with a causal associative approach. Guests who have stayed at four-star hotels in West Sumatera constitute the population, and purposive sampling technique was used to summarise the sample of this study. The sample size of this study was 98 guests who stayed at four star hotels in West Sumatera. PLS SEM (Partial Least Squere Structural Equation Modeling) is the research method used. From the results of research that has been conducted with the millennial traveler attitude variable affecting the selection four-star rating hotel. It can be explained based on this result that attitude of millennial tourists are very selective in selection four star hotels in West Sumatera to stay.